Basic Concepts of Psychiatric-Mental Health Nursing - Shives, Louise Rebraca (Philadelphia, Pennsylvania : J.B. Lippincott Company, 1994)
The ideal core text for short courses in psychiatric nursing This text clearly presents essential content and thoroughly addresses timely topics--all in consistent format and portable size. Succinet yet thorough coverage of the theory and its clinical application. This new edition includes chapters on the nursing process and eating disorders and a completely updated psychopharmacology chapter. You can rely on it to help you teach your students all the essentials, without overwhelming them.
Contents: Unit 1. Psychiatric-Mental Health Nursing. 1. Mental Health and Mental Illness. 2. Psychiatric Nursing History and Trends. 3. Legal Issues -- Unit 2. Components of Psychiatric-Mental Health Nursing. 4. The Nursing Process: Assessment of Psychiatric Patients. 5. The Nursing Process: Nursing Diagnosis and Intervention. 6. Therapeutic Interactions. 7. The Therapeutic Milieu. 8. Crisis Intervention. 9. Community Mental Health. 10. Group Therapy. 11. Family Therapy. 12. Psychopharmacology -- Unit 3. The Patient as a Person. 13. Theories of Personality Development. 14. Emotional Responses to Illness and Hospitalization. 15. Loss and Grief -- Unit 4. Nursing Interventions for Persons with Psychiatric Disorders. 16. Anxiety Disorders. 17. Anxiety-Related Disorders. 18. Human Sexuality and Sexual Disorders. 19. Ineffective Individual Coping: Alcoholism. 20. Ineffective Individual Coping: Psychoactive Substance Abuse. 21. Altered Mood: Affective Disorders. 22. High Risk for Self-Directed Violence: Suicide. 23. Altered Thought Processes: Delusional or Paranoid Behavior. 24. Altered Thought Processes: Schizophrenic Disorders. 25. Impaired Cognition: Organic Mental Syndromes and Disorders -- Unit 5. Special Populations in Psychiatric-Mental Health Nursing. 26. Disorders of Infancy, Childhood, and Adolescence. 27. Eating Disorders. 28. Child Abuse and Neglect. 29. The Abused Adult Within the Family Unit. 30. Rape and Sexual Assault. 31. Coping with Acquired Immune Deficiency Syndrome (AIDS). 32. Psychosocial Aspects of Aging. 33. Psychiatric Patients with Medical Problems/Syndromes -- Appendix A: Nursing Assessment of the Adult/Adolescent -- Appendix B: DSM-III-R Classification - Axes I and II Categories and Codes -- Appendix C: DSM-IV Classification - Draft Criteria -- Appendix D: North American Nursing Association (NANDA) List of Approved Nursing Diagnoses.
Includes bibliographical references and index.
Keywords: PSYCHIATRIC NURSING